1996
DOI: 10.1152/ajprenal.1996.270.2.f263
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated renal adenosine A1 receptors augment PKC and glucose transport but inhibit proliferation

Abstract: Adenosine A1 receptor densities were increased in cultured LLC-PK1 and OK cells by chronic treatment with the adenosine receptor antagonists 1,3,7-trimethylxanthine (caffeine, 1 mM) and 1,3-dimethyl-8-cyclopentylxanthine [cyclopentyltheophylline (CPT), < or = 0.4 mM], respectively. The A1 receptor number per cell was increased twofold by 10-day treatments with 1 mM caffeine or 0.1 mM CPT, and the sodium-coupled glucose uptake was augmented twofold by 1 mM caffeine and sevenfold by 0.1 microM CPT (higher doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…Cells-Consistent with previous reports (19,30,31) preliminary studies demonstrated the expression of PKC␣, ␤I, ␤II, and but not of PKC␦, ␥, and ⑀ in OK cells (data not shown). To determine which PKC isoforms were activated by PTH, OK cells were treated with PTH (10 Ϫ7 M) for 15 min.…”
Section: Identification Of Pkc Isoforms Activated By Pth In Oksupporting
confidence: 92%
“…Cells-Consistent with previous reports (19,30,31) preliminary studies demonstrated the expression of PKC␣, ␤I, ␤II, and but not of PKC␦, ␥, and ⑀ in OK cells (data not shown). To determine which PKC isoforms were activated by PTH, OK cells were treated with PTH (10 Ϫ7 M) for 15 min.…”
Section: Identification Of Pkc Isoforms Activated By Pth In Oksupporting
confidence: 92%
“…Conversely, prolonged exposure to antagonists up-regulate and increase the sensitivity of cardiac and brain A 1 ARs [12, 13, 14]. Concomitant regulatory changes in the G i proteins may be associated with changes in the A 1 AR receptor density [15, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant regulatory changes in the G i proteins may be associated with changes in the A 1 AR receptor density [15, 16, 17]. In vitro, 48 h treatment with non-selective AR antagonists led to up-regulation of A 1 ARs in LLC-PK1 and OK cells associated with enhanced A 1 AR-mediated responses [14]. However, there are few data available regarding the regulation of the renal A 1 ARs in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Specific receptor expression is demonstrated in different nephron segments, such as the glomeruli, the thick ascending limb and collecting duct (16) and the proximal tu-bules (17). In the proximal tubule and the cortical collecting duct, adenosine stimulates the transport of sodium and phosphate via the apical surface (18), that of sodium and bicarbonate via the basolateral symporters (19) and stimulates chloride channel activity (20).…”
mentioning
confidence: 99%